2021
DOI: 10.1038/s41438-021-00562-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of SSRs and database construction using all complete gene-coding sequences in major horticultural and representative plants

Abstract: Simple sequence repeats (SSRs) are one of the most important genetic markers and widely exist in most species. Here, we identified 249,822 SSRs from 3,951,919 genes in 112 plants. Then, we conducted a comprehensive analysis of these SSRs and constructed a plant SSR database (PSSRD). Interestingly, more SSRs were found in lower plants than in higher plants, showing that lower plants needed to adapt to early extreme environments. Four specific enriched functional terms in the lower plant Chlamydomonas reinhardti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…SSRs have been deemed as promising candidate markers for population genetics and germplasm identification in plants due to their hypervariability, high information content and codominance [ 45 , 46 , 47 ]. With the rapid development of next-generation sequencing technology, whole-genome SSR identification becomes much more effective and comprehensive [ 2 , 48 ]. In this study, whole-genome SSR identification and comparative analysis were carried out in five bamboo species including two herbaceous bamboos and three woody bamboos representing three tribes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSRs have been deemed as promising candidate markers for population genetics and germplasm identification in plants due to their hypervariability, high information content and codominance [ 45 , 46 , 47 ]. With the rapid development of next-generation sequencing technology, whole-genome SSR identification becomes much more effective and comprehensive [ 2 , 48 ]. In this study, whole-genome SSR identification and comparative analysis were carried out in five bamboo species including two herbaceous bamboos and three woody bamboos representing three tribes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers usually refer to specific DNA segments that can reflect certain differences in the genomes of individuals or populations, which can directly reveal the genetic information in the organism through DNA molecules [ 1 ]. It is widely used in cultivar identification, marker-assisted selection, and genetic diversity analysis of germplasm resources [ 2 ]. Based on the method of analyses, molecular markers can be divided into three classes: (1) non-PCR-based techniques but based on hybridization, such as restriction fragment length polymorphism (RFLP); (2) PCR-based techniques, such as random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), and simple sequences repeat (SSR); (3) sequence-based marker techniques that is single nucleotide polymorphism (SNP) [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the three species with the highest percentage of Hsf family genes were all Brassicaceae species. This phenomenon might also relate to the WGD and WGT events of the Brassicaceae species [ 49 – 51 ]. The number of Hsf gene losses was more than gene duplication in most Lycopodiophyta, Gymnospermae, and Angiospermae species, which indicated that the Hsf family genes were lost after the WGD or WGT events in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…The software also identifies VNTRS from a large genome size, locates the SSRs in the gene coding region, and statistically analyzes and plots the graphs [ 20 ]. Simple sequence repeats are short repeat DNA sequences with 1–6 bp in length, which have high polymorphism and can be used as a tool in genetic mapping, population genetics, and phylogenetic analysis [ 21 ].…”
Section: Methodsmentioning
confidence: 99%